Rotating Cylinder Turbulator Effect on the Heat Transfer of a ‎Nanofluid Flow in a Wavy Divergent Channel‎ - M. Hatami; Lijun Sun; Dengwei Jing; H. Günerhan; Peri K. Kameswaran (Journal of Applied and Computational Mechanics, 2021)
In this research study, the numerical Galerkin Finite Element Method (GFEM) is used for forced laminar convection heat transfer of Cu-water nanofluid in a divergent wavy channel including a rotating cylinder turbulator. The above boundary of the channel is in low temperatures and the bottom boundary is in hot temperatures as well as the cylinder wall temperature. It is assumed that the cylinder rotates in the cavity and makes vortexes to enhance heat transfers. The dimensionless governing equations including velocity, pressure, and temperature formulation are solved by the Galerkin finite element method. The results are discussed based on the governing factors such as nanoparticle volume fraction, Reynolds number, cylinder diameter and rotating velocity. As a main result, among the all studied parameters (Re, u, Φ and r), increasing the Re number has the most effect on heat transfer which has 4.8 and 1.6 Average Nu for the cylinder wall and wavy wall, respectively.